Estimation of turbidity coefficient in Rosal Salta, Argentina through SMART simulation model 2.9.: Collaboration with the XXIII Peruvian Symposium on Solar Energy - Sarabia, Cristian Daniel (2020)
At present, the use of solar energy applications is booming worldwide, particularly in Argentina, through the RENOVAR program. Therefore, an analysis of the solar resource is required for the purposes of a possible installation of a Photovoltaic Solar Plant. When the sun's rays reach the surface of the earth, certain obstacles are found in its path that tend to decrease the incident solar energy. In the atmosphere, there are gases and aerosols, such as atmospheric dust (volcanic ash, very fine earth, soot, etc ...) that cause solar attenuation. There are techniques to determine the available solar resource of a site, however, sometimes it is not applicable due to lack of adequate measuring equipment, whether for economic reasons, transfer, etc. Therefore, in this paper we want to show that knowing certain measured quantities directly and that are related to solar energy such as Normal Direct Irradiance (DNI), and using a simulation model such as SMART 2.9, the coefficient can be estimated of turbidity of Ångström, β, what will be the indicator of the optical thickness of the aerosols and consequently of the decrease of the solar power. To achieve the objective proposed in the previous paragraph, it was decided to work on a place in Argentina, called El Rosal, located in the municipality of Campo Quijano and in the place called “Quebrada del Toro”, which descends from the eastern face from the Puna de Atacama. It is located 3355 meters above sea level. The choice of this place was made, not only because it is a site of height in the province of Salta, but also because of the availability of DNI data measured with a pyrometer for three different times.